Hilo : the great big boom - Winick, Judd (New York : Random House, 2017)
Hilo and his friends must save the world from monsters from another dimension.
Keywords: Graphic novels; Robots -- Fiction; Extraterrestrial beings -- Fiction; Friendship -- Fiction; Monsters -- Fiction; Science fiction